2014
DOI: 10.1007/s11010-013-1941-y
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein induces cyclooxygenase-2 expression and prostaglandin I-2 release in endothelial cells through sphingosine kinase-2

Abstract: High-density lipoprotein (HDL) has a significant cardioprotective effects. HDL induces cyclooxygenase-2 (COX-2) expression and prostacyclin I-2 (PGI-2) release in vascular endothelial cells, which contributes to its anti-atherogenic effects. However, the underlying mechanisms are not fully understood. In the present study, we observed that HDL-stimulated COX-2 expression and PGI-2 production in human umbilical vein endothelial cells (HUVECs) in a time- and dose-dependent manner. These effects triggered by HDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…As with RelB expression, several of these mediators exhibited strong associations with cardiovascular alterations. Cox-2 is induced by HDL [46] and LDL [47] , and although an association between Cox-2 and blood pressure has been described [48] , [49] , our study is first to suggest a relationship with cfPWV and AIx, two measures of arterial stiffening associated with cardiovascular risk. Moreover, the positive relationship between Cox-2 and RBC diameter width is novel and may be of clinical significance, as RBC diameter width-distribution is a powerful outcome predictor in chronic and/or acute left heart failure, and in COPD, can help identify right ventricle failure [50] .…”
Section: Discussionmentioning
confidence: 52%
“…As with RelB expression, several of these mediators exhibited strong associations with cardiovascular alterations. Cox-2 is induced by HDL [46] and LDL [47] , and although an association between Cox-2 and blood pressure has been described [48] , [49] , our study is first to suggest a relationship with cfPWV and AIx, two measures of arterial stiffening associated with cardiovascular risk. Moreover, the positive relationship between Cox-2 and RBC diameter width is novel and may be of clinical significance, as RBC diameter width-distribution is a powerful outcome predictor in chronic and/or acute left heart failure, and in COPD, can help identify right ventricle failure [50] .…”
Section: Discussionmentioning
confidence: 52%
“…Hence, even though the effect of FFA4-S on PMA-induced ROS generation was significantly more profound than that of FFA4-L, catalase upregulation likely only plays a partial role in absolving acute ROS generation. While canonical signaling of GPCRs has been shown to modulate COX-2 expression patterns (3843), a recent study found that the C-terminal tail of the angiotensin-II type 1 GPCR regulated COX-2 expression in a manner independent of canonical signals, including phosphorylation of the C-terminal tail and β-arrestin recruitment (44). Rather, ATII-1R decreases COX-2 expression via direct enhancement of COX-2 ubiquitination and subsequent proteosomal degradation, an effect that was facilitated by the C-terminal tail in absence of the rest of the GPCR (44).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to NO, there is evidence to suggest that the release of the endothelium-derived vasodilator prostacyclin can be influenced by HDLs. In human umbilical vein endothelial cells, HDLs elevated cyclooxygenase-2 protein expression and thereby induced prostacyclin synthesis via a pathway that involved PKC, ERK1/2, and sphingosine kinase SphK-2 (Xiong et al 2014). The human relevance of these findings is underscored by studies demonstrating that infusion of rHDLs in hypercholesterolemic patients led to normalization of endothelium-dependent vasodilation in response to acetylcholine (Spieker et al 2002).…”
Section: Preservation Of Endothelial Functionmentioning
confidence: 97%